Extraperitoneal kidney transplantation: a comparison between children weighting ≤15 kg and >15 kg. Experience of a single institution. (22nd September 2021) - Ghidini, Filippo; De Corti, Federica; Fascetti Leon, Francesco; Vidal, Enrico; Rancan, Alessandra; Parolin, Mattia; Zadra, Nicola; Grazzini, Maurizia; Maria Antoniello, Luca; Ganarin, Alba; Maita, Sonia; Tognon, Costanza; et al.
Summary: Extraperitoneal approach is sometimes recommended for kidney transplantation (KT) in children weighting <15 kg. We hypothesized that this approach might be as successful as in patients with normal weight. Data of all consecutive KTs performed between 2013 and 2019 were retrospectively reviewed. Early outcomes and surgical complications were compared between children weighing ≤15 kg (low‐weight (LW) group) and those weighing >15 kg (Normal‐weight (NW) group). All the 108 KTs were performed through an extraperitoneal approach. The LW group included 31 patients (mean age 3.5 ± 1.4 years), whose mean weight was 11.1 ± 2.0 kg. In the LW group, —a primary graft nonfunction (PNGF) occurred in one patient (3.2%), surgical complications occurred in nine (29%), with four venous thrombosis. In the NW group, PNGF occurred in one case (1.3%), delayed graft function (DGF) in eight (10%), surgical complications in 11 (14%) with only one case of venous thrombosis. In both groups, no need for patch during wound closure and no wound dehiscence were reported. The extraperitoneal approach can be effectively used in LW children. No differences were observed in the overall complication rate ( P = 0.10), except for the occurrence of venous thrombosis ( P = 0.02). This might be related to patients' characteristics of the LW group. Abstract : This retrospective study showed that extraperitoneal approach for kidney transplantation in low‐weight children did not increase the rate of surgical complications in comparison to normal‐weight children. One‐year estimated allograft survival was similar in the two groups. Therefore, this approach can be effectively use in low‐weight children.